2022
DOI: 10.3390/cancers14020435
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Using Real-World and Translational Data to Improve Treatment Selection for NSCLC Patients Treated with Immunotherapy

Abstract: (1) Background: In advanced non-small cell lung cancer (aNSCLC), programmed death ligand 1 (PD-L1) remains the only biomarker for candidate patients to immunotherapy (IO). This study aimed at using artificial intelligence (AI) and machine learning (ML) tools to improve response and efficacy predictions in aNSCLC patients treated with IO. (2) Methods: Real world data and the blood microRNA signature classifier (MSC) were used. Patients were divided into responders (R) and non-responders (NR) to determine if the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Interestingly, high ICI scores were associated with the activation of the T-cell and B-cell receptor signaling pathways and natural killer cell–mediated cytotoxicity. Using RNA expression levels and a machine learning approach, gene expression levels were proven to be superior and independent or complementary from PD-L1 expression [ 75 , 76 ]. When developing predictive models, SCC and ADK are often considered together.…”
Section: Genomics Transcriptomics and Proteomics: Understanding The C...mentioning
confidence: 99%
“…Interestingly, high ICI scores were associated with the activation of the T-cell and B-cell receptor signaling pathways and natural killer cell–mediated cytotoxicity. Using RNA expression levels and a machine learning approach, gene expression levels were proven to be superior and independent or complementary from PD-L1 expression [ 75 , 76 ]. When developing predictive models, SCC and ADK are often considered together.…”
Section: Genomics Transcriptomics and Proteomics: Understanding The C...mentioning
confidence: 99%
“…The sequential minimal optimization algorithm, invented by John Platt, was applied to the SVM, (6) boosting is an ensemble meta-algorithm that combines several rough and moderately inaccurate models. The C50 R package contains the C5.0 classification model, which was used to optimize the predictive value with 100 trials of boosting interactions, (7) bagging, also known as bootstrap aggregation, is another ensemble meta-algorithm. This algorithm reduces the variance within a noisy dataset.…”
Section: Statisticsmentioning
confidence: 99%
“…Another study, combining four clinical and 40 radiomic features, suggested the role of the ML approach in identifying the histologic subtypes of lung cancer 6 . The ML algorithm may also help clinicians select appropriate candidates for immune checkpoint inhibitors 7 . In terms of risk stratification, an ML model that derived 34 features predicted recurrence and overall survival (OS) more accurately compared to the TNM staging system 8 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations